The Israel lobby and U.S. foreign policy - Mearsheimer, John J. (Farrar, Straus and Giroux, 2007)
Describes how the remarkable level of material and diplomatic support that the United States provides to Israel is due to the influence of the Israel lobby, which has a far-reaching impact on America's foreign policy decisions throughout the Middle East.